Kinetics, Modelling and Scaling-Up of Kojic Acid Fermentation by Aspergillus Flavus 44-1 Using Different Carbon Sources - Mohamad, Rosfarizan (2000)
Kojic acid production by Aspergillus flavus strain 44- 1 using different types of carbon source (glucose, starch hydrolysate from enzymatic hydrolysis of sago starch, sucrose, fructose and gelatinized sago starch) was carried out in 250 mL shake flask, 2 L, 8 L and 50 L stirred tank fermenters. The experimental data from batch fermentation and resuspended cell system were analysed in order to form the basis for a kinetic model of the process. Unstructured model based on logistic and Luedeking-Piret equations was found suitable to describe growth, substrate consumption and kojic acid production by Aspergillus flavus in batch and also resuspended cell system using either glucose or sucrose. From the modelling, it was found that kojic acid production by A. flavus was non-growth associated process. The kinetic parameter values for each fermenter were calculated from the modelling and they can be used to verify the experimental data using various types and concentration of carbon source. Kojic acid production (23.5 g/l) using 100 g/L sago starch in a shake flask was comparable to fermentation of glucose (32.5 g/L) and starch hydrolysate (27.9 g/L) but in the 8 L and 50 L fermenter kojic acid production was greatly reduced due to non-optimal aeration conditions. Fed-batch fermentation with intermittent feeding of concentrated sago starch (140 g/L) can be employed to improve direct fermentation of sago starch to kojic acid by about 4 times higher as compared to batch fermentation. A. flavus was also capable to utilise sucrose for kojic acid fermentation where the highest production (40.23 g/L) in 2 L fermenter was obtained at 150 g/L sucrose. Kojic acid production (10.25 g/L) was greatly reduced in fermentation using fructose as the sole carbon source. Scaling-up based on a constant impeller tip speed (1.65 m/s) together with optimal DOT and pH control strategies was successfully used for kojic acid fermentation in 50 L fermenter using glucose and sucrose as carbon sources. Kojic acid fermentation by A. flavus can be divided into two phases; growth and production phase. The culture pH during growth phase influenced the performance of kojic acid fermentation to a further extend than did the pH during the production phase. The fermentation without pH controlled (started with an initial culture pH 3) showed higher kojic acid production than single-phase pH controlled fermentation at a range of pH 2.2 - 4.0. Comparable kojic acid production to fermentation without pH controlled was obtained in two-phase pHcontrol led fermentation (started with initial culture pH, without control during growth phase and switched to 3 during production phase). Efficient conversion of glucose to kojic acid was achieved in a resuspended cell system, in a solution containing only glucose with citrate buffer at pH 3.5 and 3 0°C. The rate of glucose conversion to kojic acid was increased with increasing glucose concentration up to 100 g/L, suggesting that the biotransformation of glucose to kojic acid by the cell-bound enzymes fol lowed the Michaelis-Menten enzyme kinetic models. The value of Km and Vmax for the reaction, as determined by using Langmuir plot, was 10.042 g/L glucose and 0.076 g/L.h, respectively.